Connectivity patterns of Brazilian coral reefs associated with potential variation on thermal stress tolerance - Silva, Gabriel Lucas Xavier da; Kampel, Milton (Frontiers in Marine Science, 2022)
The rising trend in sea surface temperature presents a threat to tropical coral reefs, causing increased mass bleaching and mortality events. Brazilian reefs have been characterized as less susceptible to thermal stress, where the assessment of bleaching events based on temperature anomalies often overpredicts its actual occurrences in comparison with other regions of the global ocean. With coral reefs acclimatized to local environmental conditions, larval connectivity presents a potential role in introducing organisms adapted to different temperature conditions. In the present study, we evaluated the connectivity patterns of Brazilian coral reefs, verifying its potential influence on the variation of thermal stress tolerance supported by these communities. Connectivity was estimated based on 27-year larval dispersion simulations, from 1993 to 2019, among 180 reef sites distributed in seven ecoregions on the Brazilian continental margin. Simulations were performed using a biophysical model coupling ocean currents data and life history traits of Mussismilia hispida, a widespread stony-coral type species and one of the major endemic reef builders in the South Atlantic. The potential influence of larval connectivity on thermal stress tolerance was evaluated considering the probability of connections between each reef site, their respective bleaching thresholds, and the accumulation of sea surface temperature anomalies over 12-week periods. The results indicated that connectivity-influenced bleaching estimations were significantly closer to observations reported in the literature when compared to estimations without connectivity (p-value < 0.05). These findings present an evidence that larval connectivity may display a relevant role in the adaptation of Brazilian corals to changes in seawater temperature, leading to a potential variation of ± 0.3°C in local thermal stress thresholds. Different connectivity patterns assessed during the occurrence of El Niño–Southern Oscillation events were also observed in association with the migrations of the South Equatorial Current bifurcation. These conditions led to the disruption of connections between the Eastern and Northeastern reef sites during El Niño, and between the Northeastern and Amazon reef sites during La Niña. Ultimately, it is expected that those findings may contribute to the management of Brazilian coral reefs regarding changes in dispersal pathways and thermal stress tolerance given future climate change scenarios.